The early repolarization pattern: Echocardiographic characteristics in elite athletes. Issue 2 (14th November 2018) - Reinhard, Wibke; Trenkwalder, Teresa; Haller, Bernhard; Meindl, Christine; Schoenfeld, Julia; Kaess, Bernhard M; Hengstenberg, Christian; Schunkert, Heribert; Pressler, Axel; Halle, Martin; Scherr, Johannes
Abstract: Background: The electrocardiographic early repolarization (ER) pattern is associated with idiopathic ventricular fibrillation and increased long‐term cardiovascular mortality. Whether structural cardiac aberrations influence the phenotype is unclear. Since ER is particularly common in athletes, we evaluated its prevalence and investigated predisposing echocardiographic characteristics and cardiopulmonary exercise capacity in a cohort of elite athletes. Methods: A total of 623 elite athletes (age 21 ± 5 years) were examined during annual preparticipation screening from 2006 until 2012 including electrocardiography, echocardiography, and exercise testing. ECGs were analyzed with focus on ER. All athletes participated in a clinical follow‐up. Results: The prevalence of ER was 17% (108/623). ER‐positive athletes were predominantly male (71%, 77/108), showed a lower heart rate (57.1 ± 9.3 bpm versus 60.0 ± 11.2 bpm; p  = 0.015) and a higher lean body mass compared to ER‐negative participants (88.1% ± 5.6% versus 86.5% ± 6.3%; p  = 0.015). Echocardiographic measurements and cardiopulmonary exercise capacity in male and female athletes with and without ER largely showed similar results. Only the notching ER subtype ( n  = 15) was associated with an increased left atrial diameter (OR 7.01, 95%CI 1.65–29.83; p  = 0.008), a higher left ventricular mass (OR 1.02, 95%CI 1.00–1.03; p  = 0.038) and larger relative heart volume (OR 1.01, 95%CI 1.00–1.01; p  = 0.01). During a follow‐up of 7.4 ± 1.5 years, no severe cardiovascular event occurred in the study sample. Conclusions: In elite athletes presence of ER is not associated with distinct alterations in echocardiography and cardiopulmonary exercise. Athletes presenting with ER are rather male, lean with a low heart rate.